Fabrication and characterization of porous 3D polymer bioceramic scaffold for tissue engineering applications - Lee, Song See; Lohashenpahan Shanmuganantha,; Abu Bakar Sulong,; Mohd Reusmaazran Yusof,; Muhammad Azmi Abdul Hamid,; Ng, Min Hwei (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
This technical paper explains the fabrication and chacterization method of a three-dimensional bone scaffold composed of porous bioceramics and natural polymers for bone tissue engineering applications. In brief, hydroxyapatite (HA) and beta-tricalcium phosphate (β-TCP) were mixed in a 7:3 ratio and fabricated as the porous bioceramic framework, while gelatin or collagen was used as an additional polymer on the bioceramic framework. Various techniques have been explored for creating pores within the bone scaffold. Micro-computed tomography scan results demonstrate that sacrificial template and binder techniques successfully produce uniform porous bone scaffolds. The average porosity for the scaffolds (n=6) is 52.36% ± 3.2, with 51.27% ± 3.3 being interconnected. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirm that there is no characteristic chemical structure transformation in the bioceramic. The PO₄³⁻ and HPO₄³⁻ groups are retained in the HA/β-TCP bioceramic after sintering at a high temperature of 1300°C. Polymers are successfully incorporated into the porous bioceramic framework through negative pressure followed by positive pressure. Mechanical testing results show that the maximum compressive strength of the collagen-free bioceramic framework is 1.750 ± 0.212 MPa, while the collagen-containing bioceramic framework is higher at 1.905 ± 0.007 MPa. The corresponding maximum compressive strain for the collagen-free bioceramic framework is 1.565 ± 0.757%, whereas the collagen-containing bioceramic framework is approximately three times higher, at 5.540 ± 1.032%. In conclusion, the porous HA/β-TCP bioceramic scaffold is compatible with tissue engineering applications and can enhance the mechanical strength of the bioceramic scaffold to resemble cancellous bone mechanical strength.